Miguel de Cervantes' Don Quixote - Milton, Joyce (Woodbury, N.Y. : Barron's Educational Series, 1985)
A guide to reading "Don Quixote" with a critical and appreciative mind. Includes background on the author's life and times, sample tests, term paper suggestions, and a reading list.
Bibliography: p. 102-105.
Mode of access: Internet.
Keywords: Cervantes Saavedra, Miguel de, -- 1547-1616.